Distribution of Experimentally Increased Costs of Parental Care Among Family Members Depends on Duration of Offspring Care in Biparental Birds - Wagner, Gretchen F.; Mourocq, Emeline; Griesser, Michael (Frontiers in Ecology and Evolution, 2019)
Biparental care systems are a valuable model to examine conflict, cooperation, and coordination between unrelated individuals, as the interactions between the parents determines their fitness. Temporarily handicapping one parent induces a higher cost of providing care and is a widespread experimental technique for testing coordinated responses to changes in the costs of parental care in birds. However, dissimilarity in experimental designs of handicapping studies has hindered interspecific comparisons of the patterns of cost distribution between parents and their offspring. Here we apply a comparative approach by handicapping a parent at nests of five altricial bird species using the same experimental treatment. Across species, handicapped parents reduced their nest visitation rate, indicating increased costs of parental care for the manipulated parent. Unexpectedly, the partners of handicapped individuals did not compensate for the reduction in care, and the increased costs were subsequently passed to their offspring. The strength of this effect was mediated by the total duration of offspring care; in species with long care periods, the offspring were passed a greater share of the additional cost. This effect was evident in both changes to nest visitation rates and the body mass gain of the nestlings. Surprisingly, these responses were independent of life history pace (i.e., adult survival and fecundity). While most studies of the costs of parental care focus on the trade-off between current and future reproduction or survival (intra-individual trade-offs), our study highlights that a greater attention to inter-generational trade-offs is warranted, particularly in species with prolonged parental care. Moreover, our findings demonstrate that parental care decisions may be weighed more against physiological workload constraints than against future prospects of reproduction, supporting evidence that avian species may devote comparable amounts of energy into survival, regardless of life history pace.